Assessing Early Marriage with Adolescent Girls' Reproductive Health and Healthy Pregnancy Planning - sary, yessy nur endah; Iriyani, Tri; Siwi, Retno Palupi Yonni; Wulandari, Umianita Risca; Anggraini, Putri Dewi; Fatmawati, Rizka (Chakra Brahmanda Lentera Institute, 2025)
Background: Early marriage poses a health risk, especially if pregnancy occurs because the reproductive organs, especially the uterus and other reproductive organs, are not yet fully developed. The purpose of this study was to analyze the relationship between early marriage and adolescent girls' reproductive health and healthy pregnancy planning. Methods: This research is quantitative research. The research design used in this study was cross-sectional. The sampling technique used was total sampling, all married adolescent girls in Kraksaan Wetan Village, Probolinggo Regency, Indonesia, totaling 37 people. This study used a research instrument in the form of a questionnaire to measure general data in the form of age, education, and occupation. In addition to questionnaires for general data, there were also questionnaires used to measure specific data, such as the variables of adolescent girls' reproductive health and pregnancy planning—univariate data analysis with frequency distribution, bivariate data analysis with chi-square. Results: The results showed that the majority of respondents' reproductive health was in an unhealthy condition, with as many as 20 people (54.05%). The majority of respondents had poor pregnancy planning, as many as 23 people (62.16%). The results of data analysis with SPSS using chi square informed that the p value was 0.582 (α=0.05). Conclusion: The results showed that there is no correlation between early marriage and adolescent girls' reproductive health and healthy pregnancy planning in Kraksaan Wetan Village, Probolinggo Regency. Teenage girls should get enough information about reproductive health before marriage, and parents should delay early marriage before they are more than 19 years old.